Evaluation and improvement of Occupational Health and Safety Management Using HAZOP: A case Study in the Kiln Unit - Riny Yolandha Parapat; Ayunita Yuniar; Novianti Purnama Dewi; Yuono (PT Naureen Digital Education, 2025)
PT Indocement Tunggal Prakarsa Tbk is a leading cement producer in Indonesia, operating highly sophisticated clinker production facilities. One of the most critical units in the cement manufacturing process is the kiln, where raw meal undergoes pyroprocessing at extremely high temperatures, posing significant occupational health and safety risks. This study aims to assess the process safety risks in the kiln unit using the Hazard and Operability Study (HAZOP) method. The methodology involves identifying process nodes, analyzing potential deviations using guide words, and evaluating risks based on causes, consequences, existing safeguards, and recommended actions. The assessment identified several potential hazards such as temperature deviations, combustion failures, material blockages, and overpressure incidents, which may lead to equipment failure, production loss, or catastrophic events. Risk levels were categorized using a two-dimensional risk matrix based on severity and likelihood. The study concludes with mitigation recommendations including enhanced burner monitoring, installation of redundant safety devices, and improved maintenance programs. These findings are expected to contribute to enhancing the operational safety and reliability of the clinker production process at PT Indocement Tunggal Prakarsa Tbk.